Meditation for fidgety skeptics [compact disc, unabridged] : a 10% happier how-to book - Harris, Dan, 1971-; Warren, Jeff, 1971-; Adler, Carlye (Random House Audio : Books on Tape, 2017)
Presents a practical guide to meditation that debunks the myths, misconceptions, and self-deceptions that make many people reluctant to try it, and suggests a range of meditation practices.